Global Insights on Future Trends of Hybrid/EV Driveline Lubrication and Thermal Management - Tung, Simon C.; Woydt, Mathias; Shah, Raj (Frontiers in Mechanical Engineering, 2020)
Revised Abstract Global automotive industries have recently switched development trends from the traditional powertrain mechanical components into the digital transformation of the electrification components in advanced propulsion vehicles. This industrial impact on global development trend into automotive electrification designs has created an emerging technology for new propulsion systems such as hybrid electrical vehicles (HEV) or electrical vehicles (EV). Advanced propulsion systems resulting from global regulations are intended to improve vehicle fuel efficiency and reduce transportation-related emissions of greenhouse gases and other pollutants. In many HEV or EV advanced system designs, automotive lubri¬cants such as drivetrain fluids or thermal coolants have contact with the integrated electric motor (e-motor) and thermal management devices, which requires electrical and thermal properties to be consi¬dered in addition to conventional lubricant properties. The introduction of electrification components has been targeted for energy efficiency and long-term durability. Automotive industries have requested the adoption of the dedicated automotive lubricants or driveline fluids to meet appropriate thermal cooling requirements, offer bearing protection, ensure corrosion protection, and provide oxidation and sludge control. This review paper will provide with global insights on future automotive electrification development trends related to advanced driveline lubricants and thermal cooling fluids used in Hybrid/EV vehicles. Future research activities in advanced driveline fluids will be focused on minimizing friction loss and maximizing hybrid component durability. The major objective of this paper is to highlight the future electrification development trends and the required lubricants for advanced Hybrid/EV vehicles. The major section of this paper will be focused on the most important progress of automotive lubrication in the areas of energy efficiency, driveline reliability, cooling system design and thermal management requirements. In this review paper, new developments in thermal management fluids have been described to help promote the high-performance cooling system on electrical batteries, motors, and power electronics. In addition, global research activities using novel nanofluids for thermal cooling have the high potential for application to EV/Hybrid technologies. This paper has reviewed the state-of-art thermal management technology used for extending driving range and durability of EV/Hybrid vehicles. .